2019
DOI: 10.1080/17436753.2019.1584481
|View full text |Cite
|
Sign up to set email alerts
|

High yield synthesis of boron-based nanosheets

Abstract: We present the chemical exfoliation of magnesium diboride (MgB 2 ) by employing organic chelating agents for synthesising boron-based nanosheets in high yield. MgB 2 is a promising parent material towards realising quasi-2D forms of boron, owing to its unique layered constitution: graphenic boron planes interleaved with hexagonal arrays of Mg atoms. Chelating agents can selectively extract the interlayer Mg from MgB 2 in water, to form Mgchelant complexes. The loss of Mg results in delamination of MgB 2 into b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…They found that the reaction between MgB 2 and water is an ion-exchange process between protons and Mg cations, followed by a hydrolysis reaction . James et al introduced an alternative chelation-assisted route to delaminate MgB 2 and AlB 2 by selectively removing the Mg and Al atoms using a suitable chelating agent (Figure b). , All the above studies explored exfoliation of MgB 2 crystals in aqueous media, resulting in functionalized magnesium-deficient boron-based nanosheets with an empirical formula Mg 1– x B 2 H y O z with nanosheet thickness varying from ∼1.5 to 6 nm. It is noteworthy that the change in structure, composition, and the presence of functional groups (hydrides, oxides, and hydroxides) increased the band gap energy of MgB 2 from 2.2 meV and 7.2 meV to 4.49 eV, transforming it to an insulating material .…”
Section: Synthesis Of Metal-boride-derived 2d Nanostructuresmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that the reaction between MgB 2 and water is an ion-exchange process between protons and Mg cations, followed by a hydrolysis reaction . James et al introduced an alternative chelation-assisted route to delaminate MgB 2 and AlB 2 by selectively removing the Mg and Al atoms using a suitable chelating agent (Figure b). , All the above studies explored exfoliation of MgB 2 crystals in aqueous media, resulting in functionalized magnesium-deficient boron-based nanosheets with an empirical formula Mg 1– x B 2 H y O z with nanosheet thickness varying from ∼1.5 to 6 nm. It is noteworthy that the change in structure, composition, and the presence of functional groups (hydrides, oxides, and hydroxides) increased the band gap energy of MgB 2 from 2.2 meV and 7.2 meV to 4.49 eV, transforming it to an insulating material .…”
Section: Synthesis Of Metal-boride-derived 2d Nanostructuresmentioning
confidence: 99%
“…Many known metal-boride-derived 2D nanostructures could potentially display high mechanical strength. However, the study of their mechanical properties is in its incipient stages. ,,,, Metal-boride-derived 2D nanostructures can be utilized as advanced nanofillers to improve the strength of various polymer composites and as protective nanocoatings.…”
Section: Superconductivity In Metal-boride Nanosheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…76 OH functionalization can be simply achieved by immersing or fabricating boron nanosheets within aqueous solutions. 43,[77][78][79][80] In 2017, Kondo et al prepared hydroxyl-functionalized boron nanosheets (B-OH) by an ion exchange reaction in water. 79 The ion-exchange reaction between protons in water and some of the Mg cations was followed by a hydrolysis reaction between the HB and water, producing H 2 and Mg-decient hydroxylfunctionalized boron sheets.…”
Section: Hydroxylated Boron Nanosheetsmentioning
confidence: 99%